Sustainability of Suburban Industrial Development through Place Attachment - Liwei Lu; Dingjiang Long; Yen-Ching Chuang; Marcel Pikhart; Xiaoyan He (Salehan Institute of Higher Education, 2022)
This research uses urban space reconstruction as the entry point, discussing the characteristics of residents’ sense of place in Lingang new town, Shanghai, based on the method of factor analysis to divide the sense of place into place attachment, place identity, and place dependence. On the whole, residents’ sense of place in Lingang new town is at a common level, and the comprehensive score of residents’ sense of place in Lingang new town is